The Effect of HTAC Addition on the Efficiency of PEO in Turbulent Flow - Fakhrulddin, Sarmad K.; Abdulbari, Hayder A.; Ahmad Ziad, Sulaiman; Rafeeq, Hind A. (Informatics Publishing Limited, 2017)
Objectives: Polyethylene Oxide (PEO) is one of the most effective drag reduction additives. However, it limits and degrades under high share stress. The improvement of its Drag Reduction (DR) efficiency and degradation resistant with the addition of cationic surfactant was investigated. Methods/Statistical Analysis: PEO at concentrations of 10 and 20 ppm were mixed with a different concentration of Hexadecyltrimethylammonium Chloride (HTAC). Capillary viscometerand Rotating Disk Apparatus (RDA) were used to measure the viscosity and the %DR, respectively. Findings: The results showed an improvement in both the DR ability and degradation resistance when the complex polymer-surfactant was used, compared to the pure polymer. The maximum DR was recorded as 36% at 10ppm and 42% at 20ppm PEO and 125ppm HTAC. This improvement was due to the interaction between the micelles and the polymer. Application/Improvements: This improvement will promote the use of PEO/HTAC mixture in higher share stress flow application.